Effectiveness of Warm Compress with Lemon Therapy on Pain Intensity in Post Partum Mothers - Fince Tebai; Nur Sitiyaroh (STIKep PPNI Jawa Barat, 2023)
Aims: Knowing the effectiveness of warm compresses with lemon aromatherapy on reducing the intensity of perineal wound pain in post partum mothers Methods: Quasi experimental with one group pretest-posttest research type. The sample in this study were all postpartum mothers in March 2022 as many as 30 people, the sampling technique was accidental sampling. Results: Prior to the intervention, the majority of respondents reported moderate pain (53.3%), whereas following, the majority of them experienced light pain (60%). Warm compresses with lemon aromatherapy are beneficial in lowering the intensity of perineal wound pain in postpartum moms (p.value 0.000). Conclusion: Warm compresses with lemon aromatherapy have been shown to reduce the intensity of perineal wound pain in postpartum women. It is envisaged that by offering knowledge about pain management using warm compresses, midwives will be able to improve services in managing perineal wound pain.